Poligami Tanpa Izin Isteri Dalam Perspektif Hukum: Bentuk Kekerasan Psikis Terhadap Isteri - Rizkal Rizkal (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2019)
In general, the Law of Marriage in Indonesia adheres to the principle of monogamy, although it does not rule out the possibility for husbands to have wife of more than one person at a time, or known as polygamy. The polygamy marriage desired in Article No. 1 of 1974 concerning Marriage and in the Compilation of Islamic Law is conditional polygamy, where the husband is permitted to marry polygamy with the provisions that must meet the juridical requirements stated in the Marriage Law and KHI. One of the requirements is that there is an agreement or permission from the first wife made in writing. Polygamy without the permission of the first wife will cause conflict in the household, namely psychological violence conflict suffered by the wife. So that the wife will ask for divorce because she feels betrayed by her husband. In such circumstances, the wife will feel very aggrieved by the act of polygamy secretly, the psychological disturbance due to betrayal by the husband, and other disadvantages are the wife is not entitled to a mut'ah post-divorce from the husband, because this divorce was submitted at will the wife herself.